THE EFFECT OF THE SAHABAT KB COMMUNITY-BASED COMMUNITY EDUCATION PROGRAM ON COMMUNITY PARTICIPATION IN KANTAN VILLAGE IN PANDIH BATU DISTRICT: PENGARUH PROGRAM PENDIDIKAN MASYARAKAT BERBASIS KOMUNITAS SAHABAT KB TERHADAP PARTISIPASI MASYARAKAT DI DESA KANTAN DALAM KEC. PANDIH BATU - Iyah Retiawatir; Saputera; Saiffullah Darlan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Friends of Family Planning program is designed to increase the participation of Posyandu cadres in supporting family planning (KB) programs through a community-based approach. This study aims to analyze the influence of the program on improving the knowledge, attitudes, and skills of cadres in delivering family planning education. The research uses a quantitative approach with a pretest-posttest design. The sample consisted of 50 Posyandu cadres in Kantan Village who were of productive age (20–45 years), selected using saturated sampling techniques. Data was collected through questionnaires, observations, and documentation, then analyzed using descriptive and inferential statistics. The results showed that the average cadre participation score increased from 2.30 in the pretest to 3.69 in the posttest, with an average difference of 1,386. The Paired Samples Test yielded a t-value of 47.115 with a significance of p = 0.000, which shows a significant difference between the pretest and posttest scores. The Kolmogorov-Smirnov normality test showed normally distributed data (p > 0.05), and the Levene homogeneity test yielded a significant value of 0.228 (p > 0.05), indicating homogeneous variance. These findings prove that the Sahabat KB program is effective in increasing cadre participation, especially through intensive training based on personal and local culture. These results are relevant to Bandura's theory of social learning, which emphasizes the importance of hands-on experience and social support in behavior change. This research also supports previous research that states that community-based approaches with cadre empowerment are more effective than conventional approaches in increasing public awareness and participation in health programs. The Sahabat KB program has the potential to be replicated in other regions by considering the local socio-cultural context. The recommendations of this research include increasing government support in the form of advanced training, cadre incentives, and the integration of digital technology to expand the scope of family planning education. With the empowerment of Posyandu cadres, community-based programs such as Sahabat KB can contribute significantly in supporting the achievement of public health targets.